The Effect Of Cocoyam Tubers And Moringa Leaf Ratio On The Characteristics Of Simulated Chips - Yashika, Putu Pande Pande; Ina, Putu Timur; Putra, Nengah Kencana (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 5 No 1 (2018): Scientific Journal of Food Technology, 2018)
Moringa leaves are foods rich in nutrients such as protein, vitamin C, and ?-carotene.  The purposes of this research were to know the effect of ratio of cocoyam tuber and moringa leaf on the characteristics of simulated chips, and to know the best level of the ratio. The experimental design used was randomized block design (RBD) with the ratio of cocoyam tubers and moringa leaf as treatment, namely 100% : 0%, 95% : 5%, 90% : 10%, 85% : 15%; 80% : 20%; 75% : 25%; 70% : 30%. and 3 repetitions thenso that obtained 21 experimental unit. The results showed that cocoyam tubers and moringa leaf ratio had significant effect on the water content, ash content, protein content, vitamin C content, antioxidant capacity, flavor preferences (hedonic test), aroma level (scoring test), and taste level (scoring test) of simulated chip. Ratio from 70% of cocoyam tubers : 30% of moringa leaf is the best characteristic with water content is 1,27%, ash content is 2,47%, protein content is 3,64%, vitamin C content is 32,33 mg/100g, antioxidant capacity 2,22 mg GAEAC/kg, color rather like, flavor moringa leaf strong and rather like, texture crispy and rather like, taste moringa leaf strong and rather like and overall acceptance rather like.